Plants used for topical application from Gingee hills, Tamil Nadu, India. - Muralidharan, R; Narasimhan, D (Current Botany, 2013)
This study is a documentation of medicinal plants used for topical applications by villagers around Gingee hills of Villupuram District, Tamil Nadu, India. A total of 23 Dicot plants belong to 18 families are used as topical applications to treat various skin diseases such as sore, psoriasis, itching, scabies, eczema and other skin infections. Herbs (8 species) are the dominant life form category equal number of shrubs and trees (6 species) followed by 3 species of climbers. Generally fresh plant parts are used in the form of powder, extract and paste. Leaves are the mostly used part in the preparation of medicine. The present study concluded that the abundance of medicinally important plants is an excellent potential for discovery of novel drugs to cure various ailments.